Winners and Losers from Enclosure: Evidence from Danish Land Inequality 1682-1895 - Nina Boberg-Fazlic; Markus Lampe; Pablo Martinelli Lasheras; Paul Sharp (European Historical Economics Society (EHES), 2020)
There is a vast literature on the effects of land inequality and agrarian reforms, but little on the origins of this inequality. We exploit a new and unique parish-level database of land inequality in Denmark, from 1682 to 1895, during which period there was comprehensive land reform and enclosure. We demonstrate that inequality increased after land reform in areas with more productive land, measured using contemporary tax assessments. We instrument for land quality using glacial and post glacial sediment soil types. We propose a mechanism whereby agrarian reforms allowed areas with better soil quality to realize greater productivity gains. Malthusian mechanisms and internal migration then led to greater population increases in more fertile areas, leading to a larger share of smallholders and landless laborers. We present evidence for this mechanism in part from population density revealed by censuses. After the reforms, the geographical pattern of inequality remained strikingly constant, although population and inequality continued to grow throughout the nineteenth century.
Keywords: O13; N53; Q15; 330; Denmark; enclosures; land inequality